2016
DOI: 10.3402/iee.v6.31079
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Campylobacter jejuni infections in Sweden, November 2011–October 2012: is the severity of infection associated with C. jejuni sequence type?

Abstract: BackgroundCampylobacter jejuni is among the most frequent causes of bacterial gastroenteritis in Europe. Over 8,000 C. jejuni multilocus sequence typing sequence types (STs) have been described; ST-21 and ST-45 have been identified as the most frequent types in all human studies so far. In contrast to other STs, ST-22 has been associated with the Guillain–Barré syndrome and ST-677 was recently linked to severe systemic infections in Finland. We investigated risk factors associated with hospitalisation in indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
2
11
0
2
Order By: Relevance
“…By identifying all hospital-derived Campylobacter isolates and linking these to inpatient admissions and surveillance data we calculated the sensitivity of morbidity coding associated with Campylobacter infection to be 52%, indicating substantial measurement error. This has been demonstrated in similar settings with US [ 15 ] and Swedish [ 16 ] studies reporting appropriate use of ICD coding among hospitalised campylobacteriosis cases to be 43 and 51% respectively.…”
Section: Discussionsupporting
confidence: 65%
“…By identifying all hospital-derived Campylobacter isolates and linking these to inpatient admissions and surveillance data we calculated the sensitivity of morbidity coding associated with Campylobacter infection to be 52%, indicating substantial measurement error. This has been demonstrated in similar settings with US [ 15 ] and Swedish [ 16 ] studies reporting appropriate use of ICD coding among hospitalised campylobacteriosis cases to be 43 and 51% respectively.…”
Section: Discussionsupporting
confidence: 65%
“…However, we noted that ST50 genomes, followed by ST257, possessed overall the highest number of virulence genes, including those ones considered as typical for human pathogenic C. jejuni isolates [17]. Interestingly, Harvala et al [25] showed that patients infected with C. jejuni ST-50 or ST-257 strains were slightly more likely to be hospitalized than those infected with other STs.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, there has been a global upsurge in the rate of Campylobacter infections [1,2], and Campylobacter has emerged as one of the most significant bacteria of public health importance [3]. Globally, Campylobacter infection is a significant zoonosis, considered to be the leading cause of bacterial foodborne infection [4].…”
Section: Introductionmentioning
confidence: 99%